KONSEP DIRI REMAJA PENGGEMAR KPOP - Faqih Purnomosidi; Pramesa Nabila A (Gapenas Publisher, 2023)
interest in Korean culture starts from music, a dress style, etc. Which are increasingly prevalent in Indonesia and in various countries can affect about the formation of his self-concept. From that problem, this research aims to knowing the self-concept of a teenage K-pop fans. This research uses the method descriptive qualitative. Data collection techniques with observation, structured interviews and deep. The research subjects consisted of seven adolescents aged 12-18 years who are the K-pop fan. The results show that the K-pop does not influence teenagers in their self-concept, but a liking K-pop makes it more self-motivated by dreams and hopes made